Effectiveness of Methotrexate Versus Cyclosporine in the Management of Moderate to Severe Atopic Dermatitis- Meta-Analysis of Randomised Controlled Trials - Sadiq Malik, Sakina; Anwar, Ayesha; Akhtar, Aisha; Yousaf, Farrah; Bashir, Uzma; Malik, Saadia (Pakistan Armed Forces Medical Journal, 2024)
Objective: To compare the effectiveness of Methotrexate (MTX) versus Cyclosporine (CyA) in the patients of moderate to severe atopic dermatitis (AD) Study Design: Systematic review and Meta-analysis. Methodology: After formulating our research team and PICO question rationally, a search strategy and literature search were carried out as per Cochrane guidelines. Full-text articles were retrieved after title and abstract screening per our inclusion criteria. The whole search process was documented in the form of a PRISMA flow chart. Team members made and filed data extraction sheets, and qualitative data synthesis was performed. Afterwards, a meta-analysis was carried out, involving a total of 03 randomized controlled trials. Revman was used to process the continuous and dichotomous data collected for our outcomes. RoB 2 was used to assess the risk of bias in the included studies. Grade pro-GDT was used to summarize the findings in the table. Results: Pooled results from 3 RCTs showed that CyA in a 2.5mg/kg dose is better than MTX @0.4 mg/kg/week at 12 weeks in AD. At follow-up, MTX maintains better disease control, i.e., until 24 weeks post-treatment. MTX has a better safety profile than CyA. Conclusion: MTX and CyA are both effective drugs for moderate to severe AD, but they have their pros and cons.